2020
DOI: 10.3390/cells9081801
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-5A/B Signaling in Hematopoiesis throughout Life

Abstract: Wnt signaling is well-known to play major roles in the hematopoietic system, from embryogenesis to aging and disease. In addition to the main β-catenin-dependent pathway, it is now clear that Wnt5a and the structurally related Wnt5b are essential for hematopoiesis, bone marrow colonization and the final steps of hematopoietic stem cell (HSC) maturation via β-catenin-independent signaling. Wnt5a and Wnt5b ligands prevent hematopoietic exhaustion (by maintaining quiescent, long-term HSCs), induce the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 137 publications
(217 reference statements)
1
10
0
Order By: Relevance
“…This conclusion is supported by the observation that Wnt5 DKO resulted in increased hematopoiesis in the spleens and reduced hematopoiesis in the bone marrow of DSS-treated mice. WNT5A has been implicated in bone marrow hematopoiesis and myelopoiesis, which are largely consistent with the bone marrow phenotypes of Wnt5 DKO [14,50,51]. The strong effect of Wnt5 DKO on EMH is unexpected.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This conclusion is supported by the observation that Wnt5 DKO resulted in increased hematopoiesis in the spleens and reduced hematopoiesis in the bone marrow of DSS-treated mice. WNT5A has been implicated in bone marrow hematopoiesis and myelopoiesis, which are largely consistent with the bone marrow phenotypes of Wnt5 DKO [14,50,51]. The strong effect of Wnt5 DKO on EMH is unexpected.…”
Section: Discussionsupporting
confidence: 55%
“…Wingless-type MMTV integration site family member 5 (WNT5) consists of two members, WNT5A and WNT5B, which share 90% amino acid sequence identity [13]. These WNT5 proteins are involved in diverse physiological and pathological processes, including stem cell self-renewal, cell proliferation, differentiation, migration, adhesion, and polarity [14][15][16]. Wnt5a gene knockout (KO) causes embryonic lethality with significant development defects in mice, whereas Wnt5b KO mice show no obvious phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis on previously published data sets on human synovial membrane samples [ 50 ] confirmed that Wnt5A is overexpressed in RA samples (Additional file 1 : Figure S1). It was shown that the Wnt signaling plays critical role in immune cell regulation [ 51 53 ]. Additionally, DNA methylation data of human RA samples available on epigenome-wide association study (EWAS) datahub established that the level of CpG island DNA methylation was decreased during RA condition on the Wnt5A gene (Additional file 2 : Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was also seen for normal hematopoietic cells, where the pharmacological elimination of senescent hematopoietic stem cells counteracted the aging-dependent reduction in the regenerative potential of hematopoietic stem cells [46,47]. Furthermore, signaling through several intracellular pathways seems to be altered during aging due to intrinsic mechanisms, e.g., TGF1β, Notch, NFκB and Wnt signaling [24,[48][49][50][51]. Both the induction of senescence with an altered secretory profile and the altered intracellular signaling downstream to cell surface receptors may represent combined direct and indirect effects on hematopoiesis [12,14], including the effect of increased senescence on aging with altered mediator secretion and thereby the modulation of autocrine/paracrine circuits (Figure 1) [2,9].…”
Section: Senescence and Intracellular Signalingmentioning
confidence: 99%